Analysis Of Rice Distribution On Price Stability In Perum Bulog, West Aceh Regency - Agus Wandra; Alisman Alisman; Pola Tengah Pelawi (Return : Study of Management, Economic and Bussines, 2023)
Distribution is one of the most important marketing activities carried out in marketing, namely developing and expanding the flow of goods or services from producers to consumers in accordance with a predetermined amount and time. The choice of distribution method is a very important point, because an error in choosing a distribution method can slow down the delivery of goods and services to consumers or users. Distribution of rice is one aspect of the marketing mix that also determines the success or failure of the objectives to be achieved by Perum Bulog, West Aceh Regency in distributing rice to meet community needs. The problem discussed in this study is how the influence of rice distribution on price stability at Bulog Public Corporation in West Aceh Regency. While the aim of this research to be achieved is to determine the effect of rice distribution on price stability at Perum Bulog, West Aceh Regency. The analytical method used in this study is simple linear regression analysis, simple linear regression equation implies that in a regression equation there is one dependent variable and one independent variable. The simple linear regression method aims to prove the hypothesis on the effect of joint distribution variables on price stability at Perum Bulog, West Aceh Regency, both individually and collectively. Based on the results of the study, it shows that the effect of the distribution of rice (X) on the stability of rice prices (Y) is very significant. This is evidenced by the value of Rice Price Stability (Y) at the West Aceh District Bureau of Logistics Agency, a coefficient of determination of 0.875 (R) where this shows 87.50% is in the category of very high influence and the remaining 12.50% is influenced by other variables which is not researched.